Effects of resistance training on performance in competitive badminton players: a systematic review - Wang, Tao; Yee Guan, Ng; Amri, Saidon; Kamalden, Tengku Fadilah; Gao, Zhendong (Frontiers in Physiology, 2025)
BackgroundResistance training (RT) is critical in enhancing athletic performance by improving physical fitness and sport-specific skills. However, there is a lack of systematic evaluation regarding the effects of RT on competitive athletes. This systematic review aims to explore the evidence of the impact of RT on physical performance and badminton-specific skills among competitive badminton players, providing actionable insights for optimizing training.MethodsFive databases—Web of Science, PubMed, Scopus, EBSCOhost, and SPORTDiscus—were systematically searched to identify studies investigating RT interventions for competitive badminton players. The search used a combination of keywords related to RT, physical fitness, and badminton. This review adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA 2020) guidelines.ResultsRT interventions significantly improved power (e.g., countermovement jump, squat jump), speed (e.g., shuttle run), agility (e.g., directional changes), and endurance in competitive badminton players. Lower-limb RT demonstrated the strongest effects on jump performance, while core strength training enhanced technical stability and power transfer within kinetic chains. Upper-limb RT showed promising results in improving smash velocity and accuracy, though the evidence remains limited. Long-term interventions (>8 weeks) were more effective than shorter programs. Effective training modalities included plyometrics, eccentric overload, and functional core exercises.ConclusionRT programs tailored to the physical and technical demands of badminton can significantly enhance athletic performance, particularly in high-intensity scenarios like offensive strokes and rapid directional changes. These findings highlight the importance of integrating RT into badminton-specific training regimens. Future research should focus on long-term RT effects and its impact on advanced skill execution.Systematic Review Registrationidentifier CRD42024559831.